Efficient and stable inverted planar perovskite solar cells using dopant-free CuPc as hole transport layer. (20th May 2018) - Han, Jinghui; Tu, Yuxue; Liu, Zhiyong; Liu, Xingyue; Ye, Haibo; Tang, Zirong; Shi, Tielin; Liao, Guanglan
Abstract: Flexible perovskite solar cells (PSCs) such as inverted PSCs are gaining increasing attention due to their wide range of potential applications, while the selection of stable, high conductivity and energy level suitable hole transport layers (HTLs) is still challenging. Here we introduce dopant-free copper phthalocyanine (CuPc) as HTL in inverted planar PSCs, and demonstrate improved photovoltaic performance and increased stability with high reproducibility and uniformity compared to the PEDOT:PSS based devices. The champion efficiency of PSCs is achieved by 15.4% on rigid substrates and 12.8% on flexible substrates, respectively. The flexible devices also exhibit excellent bending stability, retaining ∼85% of the original power conversion efficiency (PCE) after 3000 bending cycles at r = 5 mm without encapsulation. Our study provides a new strategy for fabricating cost-effective, scalable and flexible PSCs with high efficiency, little hysteresis, and excellent stability.